Digital Acculturation or Displacement?: Examining the Link Between Social Media and Well-Being - Guan, Shu-Sha Angie (Frontiers in Human Dynamics, 2021)
The current study applies digital media and acculturation models to assess the links between offline social connection, online social media use, and well-being. Acculturation research suggests that intercultural contact can create conflict that individuals must resolve using four acculturations strategies: marginalization, separation, assimilation, or integration. It suggests that those who fare best adopt strategies in which they maintain heritage connection, identity and values (e.g., offline, face-to-face [F2F] social connection) while also connecting with people and norms in the new context (i.e., online). The social interaction displacement hypothesis suggests that high media use that displaces in-person social interaction (i.e., assimilation strategy) can lead to poor outcomes. The results from a survey of 60 college students (Mage = 22.02, SD = 3.54; 73.3% female) suggest that individuals who maintain high offline, F2F social interaction (i.e., separation strategy) fared better than those who adopted assimilation or even integrations strategies. The findings have implications for people who spend more time online, perhaps at the expense of in-person socialization, and introduce novel opportunities for the understanding of the link between social media and poor mental health outcomes.